2014
DOI: 10.2152/jmi.61.65
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in diagnostic performance of the revised total testosterone measuring system in Japanese women with polycystic ovary syndrome

Abstract: Hyperandrogenemia has become an important factor in the diagnosis of polycystic ovary syndrome (PCOS), in Japan as well as Western countries, since the Japanese PCOS diagnostic criteria were revised in 2007. The revised electrochemiluminescence immunoassay (ECLIA) reagent for total testosterone (T) (ECLusys TESTO II; New T assay), which has lower cross-reactivity with DHEA-S than the previous reagent (ECLusys TESTO I; Old T assay), has recently been developed. We studied the improvement between New and Old T a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Previous studies in vitro have demonstrated that CAG repeat number shows an inverse correlation with AR activity [9][10][11][12][13][14]. Hence, it's not difficult to understand that shorter CAG repeats, increasing AR activity, are associated with prostate cancer [15,16], hirsutism [17] and hyperandrogenism in ovary [18,19], while longer CAG repeats, decreasing AR activity, are related to hypoandrogenicity [20] and male infertility due to impaired sperm production [10,21]. CAG tracts beyond the normal range (>40 CAG repeats) leads to Kennedy's syndrome, a fatal neuromuscular disease [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in vitro have demonstrated that CAG repeat number shows an inverse correlation with AR activity [9][10][11][12][13][14]. Hence, it's not difficult to understand that shorter CAG repeats, increasing AR activity, are associated with prostate cancer [15,16], hirsutism [17] and hyperandrogenism in ovary [18,19], while longer CAG repeats, decreasing AR activity, are related to hypoandrogenicity [20] and male infertility due to impaired sperm production [10,21]. CAG tracts beyond the normal range (>40 CAG repeats) leads to Kennedy's syndrome, a fatal neuromuscular disease [22].…”
Section: Introductionmentioning
confidence: 99%
“…Adrenal function was also within normal limits, as were her insulin level, blood glucose level, and lipid metabolism (data not shown). These finding met the diagnostic criteria for PCOS 3 . As soon as the diagnosis was confirmed, the dosage of VPA was reduced by 50% for 1 month, after which administration was terminated.…”
Section: Case Reportmentioning
confidence: 58%
“…The symptoms of PCOS include menstrual disorders (including amenorrhea), infertility, miscarriage, and hirsutism 2 . PCOS is characterized by any 2 of the following: oligomenorrhea or amenorrhea, hyperandrogenism or hyperandrogenemia, and polycystic ovaries 2,3 . The diagnostic criteria for PCOS define hyperandrogenemia as elevated serum total testosterone, free testosterone, or androstenedione levels 3 .…”
Section: Introductionmentioning
confidence: 99%
“…This study enrolled 45 women with ovulatory disorders (including 21 women with PCOS, as diagnosed by the Japanese PCOS criteria, 13,14 all of which also meet the Rotterdam criteria, 15 and a BMI of ≥25. All of them did not have menstruation for at least 2 months.…”
Section: Participantsmentioning
confidence: 99%